RECONVERSIÓN PRODUCTIVA Y CONDICIONES DE VIDA DE LA POBLACIÓN RURAL EN COSTA RICA, 1990-2018 - Blanco Obando, Edgar Eduardo (Universidad de Costa Rica, 2019)
In this article, it has been analyzed how the economic policy of productive transformation, applied between 1990-2018 in Costa Rica, has affected the social welfare of rural population. After analyzing a large number of scientific and specialized documents, it has been demonstrated that productive transformation has not solved the main problems of Costa Rica´s rural population, which is the major objective of rural development programs.